Cultural Keyword ‘Eling’ in Javanese and Its Implication in Javanese Society - Ounu Zakiy Sukaton (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2019)
Cultural keywords are important information that we can use to understand how people who use those words see life from their perspective. The same can be said about the Javanese community. Some of their words and concepts are exclusive to their own and they can give hindsight to how the Javanese people perceive their life. In order to analyse the meaning behind cultural keywords, Natural Semantic Metalanguage (NSM) is used in this article. The data was taken from several social media posts to illustrate the core meaning of the word ‘eling’. An explication is proposed for the word ‘eling’ as well as a brief conclusion about the multiple meaning of ‘eling’ and its usage.